2016
DOI: 10.1002/polb.24003
|View full text |Cite
|
Sign up to set email alerts
|

The coalescence of polystyrene in correlated binary solvents

Abstract: The solution behavior of solvophobic polymers is crucial to the development of polymer coatings and polymeric drug delivery vehicles. In this article, the role of dipolar interactions is investigated in the solvophobic coalescence of polystyrene in binary correlated polar solvent mixtures. A simple model for coalescence thermodynamics is derived from correlations between thermally rotating dipole moments in the solvent. The stabilizing correlations lost to the solvent due to a solute's presence give rise to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…This suggests that the driving mechanism is outside of the conceptual-lock of hydrogen bonding (or at least the domination aspect thereof). Previously, we have observed that dipolar dispersion forces contribute significantly to the thermodynamics at solid and liquid–vapor interfaces, as well as in bulk systems. ,, Therefore, these same forces were investigated for the complex dipolar MeOH–water mixtures. Our methods allow the computation of dipolar interactions as a pair-interaction in solution between molecules (eq ).…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the driving mechanism is outside of the conceptual-lock of hydrogen bonding (or at least the domination aspect thereof). Previously, we have observed that dipolar dispersion forces contribute significantly to the thermodynamics at solid and liquid–vapor interfaces, as well as in bulk systems. ,, Therefore, these same forces were investigated for the complex dipolar MeOH–water mixtures. Our methods allow the computation of dipolar interactions as a pair-interaction in solution between molecules (eq ).…”
Section: Resultsmentioning
confidence: 99%
“…Complex solvation phenomena occur in polar liquids, which include specific ion effects in aqueous 1,2 and nonaqueous systems, 3 solvophobic effects that reduce the solubility and drive the coalescence of apolar species immersed in polar liquids 4,5 as well as the high surface energies of polar liquids. 6 The mechanistic driving force behind these phenomena is not well understood but is likely related to the perturbation of the liquid's structure by solutes and interfaces 7 and how that enhances or diminishes intermolecular correlations.…”
Section: Introductionmentioning
confidence: 99%
“…By this definition, the conformation of a single polymer chain in the brush is not independent of its neighbors, meaning that transitions in polymer conformation tend to be rapid, communal, and dramatic across the range from fully swollen to collapsed. The stimuli that cause these polymer transitions come in many forms, such as environmental (pH, [ 1 ] ionic strength, [ 2 ] solvent, [ 3 ] temperature, [ 4 ] solutes [ 5 ] ) and applied (direct contact, [ 6 ] shear flow [ 7 ] ). As the polymers undergo conformational transitions, the interactions between chains and the orientation of surface‐exposed groups changes significantly.…”
Section: Introductionmentioning
confidence: 99%